Hip Instability Leading to Metallosis, Polyethylene Wear, and Failure of an Oxinium Femoral Head: A Case Report and Review of Literature - Mahmoud, Ahmed Nageeb; El-Husseini, Timour F.; Osman, Wael S.; Maziad, Ali M. (The Journal of Hip Surgery, 2021)
Oxinium is a zirconium metal alloy with an oxidized (ceramicized) surface that aims to mimic the superior wear properties of a ceramic femoral head while maintaining the high strength of metal-bearing surfaces. There are several reports that illustrate the wear and/or failure of Oxinium femoral heads following abnormal head contact with metal cup, with only a few studies reporting on the occurrence of metallosis. We present a case of metallosis and failure of Oxinium femoral head following two incidents of hip instability and one closed reduction. Successful revision was performed with cemented cup and metal femoral head, with 68 months of follow-up. We aimed to highlight the importance of achieving stable and well-oriented hip components when using Oxinium-bearing surfaces and to present a short literature review regarding the wear of oxidized zirconium-bearing surfaces in hip arthroplasty.
Keywords: Oxinium; metallosis; total hip arthroplasty; wear; instability